Physiological challenging of stress in rats with zeaxanthin - Wissam Sajid Hashim (Muthanna Medical Journal, 2022)
This study was to rule whether the carotenoid zeaxanthin can withstand against the stress caused by hydrogen peroxide in rats. Three groups of twelve adult male Wistar rats were depended. The results hinted that zeaxanthin could significantly lower the elevated lipids LDL, TC, TAG, and VLDL caused by H2O2 and to elevate the HDL level. Besides, H2O2 caused a significant elevation in the serum anti-oxidant enzymes GPx, SOD, and CAT beside the stress marker MDA and when zeaxanthin was offered as a concomitant with H2O2, it caused a significant declination in these parameters.